SEG Technical Program Expanded Abstracts 2000 2000
DOI: 10.1190/1.1815658
|View full text |Cite
|
Sign up to set email alerts
|

Varying the effective mass of geophones

Abstract: Traditionally, acquiring seismic data has rested on the assumption that geophone mass should be as small as possible. When Steeples and coworkers in 1999 planted 72 geophones automatically and simultaneously with a farm tillage implement, the effective mass of each of the geophones was significantly increased. We examined how the mass of a geophone affects changes in traveltime, amplitude, frequency, and overall data quality by placing various external masses on top of 100-Hz vertical geophones. Circular barbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Ground undulations smaller than the length of a segment of channel iron caused the geophone spikes to be planted at depths that varied slightly. Second, when the geophones were planted automatically, the mass of the Autojuggie II improved the geophone-to-ground coupling of some of the receivers relative to the others, similar to Spikes et al [2001b]. Combined with the slightly different planting depths, the travel times of the events differ from the corresponding events on the control-line shot gather.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Ground undulations smaller than the length of a segment of channel iron caused the geophone spikes to be planted at depths that varied slightly. Second, when the geophones were planted automatically, the mass of the Autojuggie II improved the geophone-to-ground coupling of some of the receivers relative to the others, similar to Spikes et al [2001b]. Combined with the slightly different planting depths, the travel times of the events differ from the corresponding events on the control-line shot gather.…”
Section: Resultsmentioning
confidence: 89%
“…Hoover and O'Brien [1980] and Krohn [1984] showed that the mass of a geophone affects its capability to respond to earth motion. However, Spikes et al [2001b] showed that increasing the effective mass of a geophone did not detrimentally affect its ability to record seismic information. During recording, the cylinders were disconnected from the channel-iron segments immediately after planting the attached geophones.…”
Section: Field Proceduresmentioning
confidence: 99%
“…There is also a slight predicted decrease in the observed amplitude. Spikes et al (2001) referred, in their experiments with weights applied on top of geophones, that the result of increasing the effective mass did not seem to be detrimental to the acquisition of high quality near-surface seismic data. They also concluded that adding certain masses decreased the amplitude and frequency of the signal.…”
Section: E X P E R I M E N T a L D A T Amentioning
confidence: 99%
“…theses Blair, 2003;Johnson, 2003), a Ph. D. dissertation , and published in refereed scientific journals (Schmeissner et al, 2001;Spikes et al, 2001a,b;Tian et al, 2003) and conference proceedings (Spikes et al, 2000(Spikes et al, , 2001. Additional manuscripts are either in review or in press.…”
Section: Statusmentioning
confidence: 99%
“…At the selected test site, spike length did not appear to be a significant factor in terms of data quality. Spikes et al (2001) showed that effective geophone mass (i. e., downward force) does not have a significant effect on data quality. The present Autojuggie weighs about 3200 lbs., which provides a downward pressure of only about 44 lbs.…”
Section: Statusmentioning
confidence: 99%